2008
DOI: 10.1111/j.1365-2109.2008.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fermented fish-offal in the formulated diet of the freshwater catfishHeteropneustes fossilis

Abstract: A 60-day feeding trial was conducted to test the e¡ect of partial replacement of ¢shmeal by ¢sh-o¡al (FO) in the diet for the freshwater cat¢sh Heteropneustes fossilis. Three isonitrogenous (31.4% CP) diets were formulated to include a reference diet (T1) with 40% ¢shmeal (FM) and 0% FO and two supplementary diets: one (T2) containing 25% FM and 25% FO and another (T3) containing 20% FM and 30% FO. The FO was fermented along with mustard oil cake and rice bran before using it as an ingredient in the preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
6
30
2
2
Order By: Relevance
“…The results of this study indicated that it is possible to totally replace FM with MFV in African catfish diet without affecting growth performance, thus confirming previous studies findings that animal by-product meals are acceptable protein sources for replacement of fishmeal in catfish diet [2,6,11,19,29,34]. Previous studies have reported beneficial effects [34,[62][63][64] but also adversely effects [65][66][67][68][69] of using MFV as protein sources in diets for several species. According to several studies, the poorest performance of fish fed alternative protein sources are due to the low feeding intake and low digestibility and imbalance of essential amino acids of diet [61,70].…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study indicated that it is possible to totally replace FM with MFV in African catfish diet without affecting growth performance, thus confirming previous studies findings that animal by-product meals are acceptable protein sources for replacement of fishmeal in catfish diet [2,6,11,19,29,34]. Previous studies have reported beneficial effects [34,[62][63][64] but also adversely effects [65][66][67][68][69] of using MFV as protein sources in diets for several species. According to several studies, the poorest performance of fish fed alternative protein sources are due to the low feeding intake and low digestibility and imbalance of essential amino acids of diet [61,70].…”
Section: Discussionsupporting
confidence: 86%
“…To minimize nutrient leaching, only fresh and intact faeces were collected and dried to a constant weight at 60°C in an oven. Apparent protein digestibility (APD %) of the diet was calculated from the proportion of Cr and protein in the diet and faeces following the methods described by Ellestad et al (2002) and Mondal et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…The FCR of 1.64-2.30 was obtained in guppy fed diets containing various animal protein sources (Table 4). Using different animal protein sources, the great variations in FCR values were reported by earlier workers for different fish species viz., 1.52-3.35 with silkworm pupae in carps (Nandeesha et al 2000;Mahata et al 1994;Nandeesha et al 1988;, 1.89-2.50 with slaughter house waste in L. rohita (Singh et al 2006), 1.58-2.27 with poultry by-product meal (Rawles et al 2006;Rawles et al 2011), 1.70-2.65 with turkey meal (Thompson et al 2007;Muzinic et al 2006), 1.86-3.10 with blood meal (Saha and Ray 1998), 1.20-1.87 with fermented fish offal (Mondal et al 2008;Mondal et al 2011), 1.60-1.90 with tuna-by product meal (Tekinay et al 2009) and 2.01-2.32 with snail offal meal (Okanlawon and Oladipupo 2010). The wide variations observed in FCR values may be due to source of animal protein used in the diet, species of fish cultured (fresh/ marine/brackishwater/tropical/temperate), feeding habits of fish (herbivorous/carnivorous/omnivorous) and the fish rearing system (static/flow-through/recirculatory).…”
Section: Discussionmentioning
confidence: 96%
“…The diet resulting higher SGR is always considered as nutritionally balanced diet. As reported by earlier workers, the SGR values also varied widely with dietary animal protein sources for various fish species (0.84-3.07 in silkworm pupae, Nandeesha et al 1990, Mahata et al 19940.59-0.99 in chicken offal, Khan and Jafri 1992;3.20 in mealworm, Ng et al 2001;1.73-2.48 in slaughter house waste meal, Singh et al 2006;0.66-1.45 in poultry by product, Yigit et al 2006, Rawles et al 20110.51-0.71 in garden snail meal, Sogbesan et al 2006;0.65-2.05 in turkey meal, Muzinic et al 2006, Thompson et al 20070.62-0.98 in earthworm, Sogbesan et al 2007;1.4-1.7 in poultry by-product, Shapawi et al 2007;2.70-3.10 in fisheries by-catch and processing meal waste, Goddard et al 2008;1.05-1.36 in fermented fish offal, Mondal et al 2008, Mondal et al 20110.60-0.70 in tuna by-product meal, Tekinay et al 2009). The present SGR values of 3.57-4.31 observed in guppy is better than the previous reported values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation